Inclusive Education: Cooperation Between Class Teachers, Special Teachers, Parents to Optimize Development of Special Needs Childrens - Ariani, Alpha; Wahyudi, Mochamad; Rugaiyah, Rugaiyah (International Journal for Educational and Vocational Studies, 2019)
This study aims to find out the collaboration between class teachers, special guidance teachers, and parents of children with special needs. In addition, it also knows the optimization of the developmental aspects of children with special needs which include academic attitudes, social skills, emotions, and independence. This study used qualitative research methods. The process of data collection is done using the method of interviews, observation, and documentation study. Data analysis using the model presented by Miles and Huberman includes the process of data reduction, data presentation, and drawing conclusions based on facts in the field. The results of the study show that good collaboration between classroom teachers, special guidance teachers, and parents in the process of education in schools strongly supports the development of children with special needs. The development of aspects of social skills is more prominent than the development of aspects of academic attitudes, emotional development, and independence.